Supplying hotels ? quality and reliability - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2008)
A purchasing officer from a luxury hotel explains the criteria that farmers must meet to supply this well-paid market